PERANCANGAN SISTEM INFORMASI PEMBAYARAN SERVIS ELEKTRONIK TOKO MS COMPUTER MENGGUNAKAN JAVA DAN MYSQL - Harry Dhika; Merita Ayu Sri Maharani; Atikah Atikah (SINTECH (Science and Information Technology) Journal, 2021)
The problems in the MS Computer Store are the difficulty of officers in data collection of incoming goods, service payment transaction data and the absence of an information system related to customer service data collection. With this problem, an information system is needed to make it easier for officers in the process of data collection which will be stored safely in the database and printing of reports that will be submitted to the Manager of MS Computer. The purpose of this research is to design an electronic service payment application system which is expected to make it easier to process data and transactions properly and quickly. The system is designed using the Research and Development Method because it is more precise. Where in building this system used System Design tools, namely Data Flow Diagrams (DAD), Context, Zero and Detailed and using the Java programming language with Netbeans and MYSQL Database using Xampp. The results of research that has been carried out at the MS Computer Store, with the existence of an electronic service payment application system replacing the old system, the current employee performance becomes more effective and efficient. Admin does not need to input service data or electronic service payments manually, because this application system provides service data entry forms and payment data.